Assessment of Able-Bodied and Amputee Cyclists’ Aerodynamics by Computational Fluid Dynamics - Forte, Pedro; Morais, Jorge E.; Barbosa, Tiago M.; Marinho, Daniel A. (Frontiers in Bioengineering and Biotechnology, 2021)
The aim of this study was to compare the aerodynamics of able-bodied and amputee cyclists by computational fluid dynamics. The cyclists´ geometry was obtained by a 3D scanner. Three CAD models were created as able-bodied, transtibial (Tt) and transradial (Tr) amputees. Numerical simulations were conducted up to 13 m/s with increments of 1m/s to assess drag force. The drag ranged between 0.36 N and 39.25 N for the able-bodied model, 0.36 to 43.78 for the Tr model and 0.37 to 41.39 N for the Tt model. The pressure drag ranged between 0.20 N and 22.94 N for the normal model, 0.21 to 28.61 for the Tr model and 0.23 to 28.02 N for the Tt model. The viscous drag ranged between 0.16 N and 15.31 N for the normal model, 0.15 to 15.17 for the Tr model and 0.14 to 13.38 N for the Tt model. The rolling resistance was higher on the able-bodied (2.23 N), followed by the Tr (2.20 N) and Tt (2.17 N) models. As a conclusion, the able-bodied cyclist showed less drag, followed by the Tt and Tr models, respectively. The rolling resistance presented higher values in the able-bodied, followed by the Tr and Tt models.